Crystal structure of a novel Kunitz type inhibitor, alocasin with anti‐Aedes aegypti activity targeting midgut proteases. Issue 12 (3rd July 2018) - Vajravijayan, Senthilvadivel; Pletnev, Sergei; Pletnev, Vladimir Z; Nandhagopal, Narayanasamy; Gunasekaran, Krishnasamy
Abstract: BACKGROUND: The pesticidal properties of many Kunitz‐type inhibitors have been reported previously; however, the mechanism of action is not well established. In this study, the activity of alocasin against Aedes aegypti is demonstrated and the structure–activity relationship of this Kunitz‐type inhibitor is explained through X‐ray structure analyses. RESULTS: Alocasin was purified from mature rhizomes of Alocasia as a single polypeptide chain of ∼ 20 kDa. The structure at 2.5 Å resolution revealed a Kunitz‐type fold, but variation in the loop regions makes this structure unique; one loop with a single disulfide bridge is replaced by a long loop with two bridges. Alignment of homologous sequences revealed that this long loop contains a conserved Arg residue and modeling studies showed interaction with the catalytic Ser residue of trypsin‐like enzymes. The anti‐ Aedes aegypti activity of alocasin is examined and discussed in detail. The in vitro activity of alocasin against midgut proteases of Aedes aegypti showed profound inhibition. Further, morphological changes in larvae upon treatment with alocasin revealed its activity against Ae. aegypti . Docking studies of alocasin with trypsin (5G1), a midgut protease involved in the development cycle and blood meal digestion, illustrated its insecticidal activity. CONCLUSION: The three‐dimensional structure of alocasin was determined and its structure–function relationship established for its anti Ae. aegypti activity. © 2018 Society of Chemical Industry Abstract : There is a continuing need to explore alternatives for more natural bioactive insecticides. This article presents the three‐dimensional structure of alocasin and structure–function relationship for its anti‐ Aedes aegypti activity.